2009
DOI: 10.1510/icvts.2008.192757
|View full text |Cite
|
Sign up to set email alerts
|

Is repeated administration of blood-cardioplegia really necessary?

Abstract: The aim of this work was to question the necessity of repeated administration of warm blood cardioplegia in modern cardiac surgery. A consecutive series of 4014 patients underwent cardiosurgical procedures in the period from January 2001 to December 2006 in our centre, where modified Calafiore warm blood-cardioplegic solution was used. 1708 patients received a single shot of cardioplegia instead of repeated blood cardioplegia (every 20 min). A multivariate analysis was performed using logistic regression model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Minatoya et al [ 15 ] reported that intermittent warm BC provided 30 minutes of safe ischemia in patients who underwent coronary bypass surgery. Ghazy et al [ 16 ] showed that the protection of the first shot of warm cardioplegia might be > 20 minutes. Later, the same group reported that the time interval between the warm cardioplegic doses could be safely increased to > 35 minutes [ 17 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Minatoya et al [ 15 ] reported that intermittent warm BC provided 30 minutes of safe ischemia in patients who underwent coronary bypass surgery. Ghazy et al [ 16 ] showed that the protection of the first shot of warm cardioplegia might be > 20 minutes. Later, the same group reported that the time interval between the warm cardioplegic doses could be safely increased to > 35 minutes [ 17 ] .…”
Section: Discussionmentioning
confidence: 99%
“…(2018) demonstrated that the safe interval for infusion of normothermic blood cardioplegia was 13 minutes. 15 Ghazy T. et al (2009) indicated that "the standard in the literature is still the repeated infusion of cardioplegic blood solution every 15 minutes". 16 Molina GR et al (2018) noted that once cross-clamp is applied, and infusion of cold blood cardioplegia has begun, typical ECG changes can be observed in one to two minutes time and an isoelectric ECG recording is obtained after 3 to 4 minutes that lasts for at least 90 minutes or longer.…”
Section: Discussionmentioning
confidence: 99%
“…It was 5 min in 1992 ( 79 ), 10–15 min in 1995 ( 73 75 ), 30 min in 2000 ( 80 ), or even more. Single shot warm blood cardioplegia was used for aortic clamp time between 29 and 47 min ( 81 ).…”
Section: Warm Cardiac Surgery the Adult Experiencementioning
confidence: 99%